2018
DOI: 10.1210/en.2018-00726
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Cortisol Metabolism in Equine Pituitary Pars Intermedia Dysfunction

Abstract: Equine Cushing disease [pituitary pars intermedia dysfunction (PPID)] is a common condition of older horses, but its pathophysiology is complex and poorly understood. In contrast to pituitary-dependent hyperadrenocorticism in other species, PPID is characterized by elevated plasma ACTH but not elevated plasma cortisol. In this study, we address this paradox and the hypothesis that PPID is a syndrome of ACTH excess in which there is dysregulation of peripheral glucocorticoid metabolism and binding. In 14 horses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 48 publications
0
20
0
2
Order By: Relevance
“…[46][47][48] Previous work has shown that PPID horses treated with DA agonists have decreased levels of POMC peptides and ACTH in the PI, and cortisol concentrations in plasma. 14,46,49 Our data demonstrate that pergolide treatment also re-establishes levels of DA and TH in PI tissue of PPID horses.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…[46][47][48] Previous work has shown that PPID horses treated with DA agonists have decreased levels of POMC peptides and ACTH in the PI, and cortisol concentrations in plasma. 14,46,49 Our data demonstrate that pergolide treatment also re-establishes levels of DA and TH in PI tissue of PPID horses.…”
Section: Discussionmentioning
confidence: 54%
“…50 There is mounting evidence that PPID is a neurodegenerative disorder characterized by loss of DA neurons and, subsequently, dopaminergic input to PI melanotropes. The lack of endogenous DA-mediated inhibition of PI POMC production in PPID-affected equids, may also result in multiclonal expansion which could explain (in addition to the uctuation of cortisol release in the blood stream) 14 PI hyperplasia and formation of multifocal adenomas. Dorsal expansion of the PG and compression of surrounding structures including the hypothalamus and infundibular stalk might explain, in part, loss off PVN dopaminergic axon terminals which decreases the concentration of DA and DA-metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of DA agonists is a logical therapeutic strategy for horses with PPID [ 46 48 ], which our data further reinforce. Previous work has shown that PPID horses treated with DA agonists have decreased levels of POMC peptides and adrenocorticotropic hormone (ACTH) in the PI, and cortisol concentrations in plasma [ 14 , 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, α-MSH and β-endorphin are capable of inducing a six-fold increase in the steroidogenic properties of ACTH [ 13 ]. Thus, a small increase in ACTH coupled with larger increases in potentiating peptides, α-MSH and β-endorphin, may be sufficient to stimulate adrenocortical steroidogenesis, resulting in increased plasma cortisol levels and loss of circadian rhythmicity of cortisol secretion [ 10 , 14 ]. Hence, horses with PPID are commonly referred to as having equine Cushing’s disease.…”
Section: Introductionmentioning
confidence: 99%